1995
DOI: 10.1177/1077727x950241002
|View full text |Cite
|
Sign up to set email alerts
|

Work‐Family Conflict and the Quality of Family Life: Specifying Linking Mechanisms

Abstract: This study evaluated a conceptual model that specified relationships between work and family demands, work‐family conflict, stress, and the quality offamily life. Usinga sample of 328female and 187 male working parents, path analysis indicated that the intersect of structural and psychological characteristics of work andfamily was related to work‐family conflict, influenced stress, and eventually predicted the quality offamily life. Also, as expected, the linkages between work andfamily variedfor mothers and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Only high levels of work-parent, work-spouse and work-domestic interference are associated with low levels of life satisfaction, indicating that when individuals' work interferes with their relationships with their spouse and children and their domestic activities, their levels of satisfaction in life decrease. These results are also in accordance with previous research Lingard & Francis, 2005;Montgomery et al, 2006;Weigel et al, 1995).…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Only high levels of work-parent, work-spouse and work-domestic interference are associated with low levels of life satisfaction, indicating that when individuals' work interferes with their relationships with their spouse and children and their domestic activities, their levels of satisfaction in life decrease. These results are also in accordance with previous research Lingard & Francis, 2005;Montgomery et al, 2006;Weigel et al, 1995).…”
Section: Discussionsupporting
confidence: 96%
“…household demands), autonomy, work and family pressure and parental demands (Boyar et al, 2007;Fu & Shaffer, 2001;Greenhaus & Powell, 2003;Keene & Reynolds, 2005;Voydanoff, 2005b). Consequences related to WFC include emotional exhaustion, depersonalisation, decrease in quality of life and quality of family life, impaired career outcomes, depression, decrease in job satisfaction, decrease in organisational commitment and decrease in life stress (Aryee, Srinivas & Tan, 2005;Choi, 2008;Greenhaus, Collins & Shaw, 2002;Lingard & Francis, 2005;McLean, 2002;Montgomery et al, 2006;Nikandrou, Panayotopoulou & Apospori, 2008;Weigel, Weigel, Berger, Cook & DelCampo, 1995).…”
Section: Relations With Causes and Consequencesmentioning
confidence: 95%
“…It has been found that satisfaction with spouse is an important predictor for quality of life of women but not so for men (Berry & Williams, 1987). Thus, since women experience the roles of a spouse, a parent, a family business worker, and an off-farm worker differently than men, it is important to investigate the role of conflict and tensions separately by gender (Weigel et al, 1995).…”
Section: Gender Differences and The Unit Of Analysismentioning
confidence: 98%
“…Past studies have indicated that although the demands of multiple roles have an impact on an individual's quality of life by increasing stress levels and compromising physical health (Erickson & Ritter, 2001;Weigel, Weigel, Berger, Cook, & DelCampo, 1995), they also bring rewards such as more power in a relationship, higher self-esteem, higher levels of consumption, and an increase in human and family capital (Carlson, Derr, & Wadsworth, 2003;Hyde & Kling, 2001). Positive spillover between employment and family has been largely overlooked in empirical research, regardless of consistent evidence indicating that most employed adults believe that the benefits of combining employment and family outweigh the burdens or strains (Grzywacz, Almeida, & McDonald, 2002).…”
Section: Theoretical Framework: Multiple Role Conflictmentioning
confidence: 99%